A web‐based calculator combining Geriatric Nutritional Risk Index (GNRI) and Tilburg Frailty Indicator (TFI) predicts postoperative complications among young elderly patients with gastric cancer. Issue 3 (6th February 2023) - Miao, Xueyi; Ding, Lingyu; Hu, Jieman; Zhu, Hanfei; Zhao, Kang; Lu, Jinling; Jiang, Xiaoman; Xu, Qin; Zhu, Shuqin
Abstract : Aim: Nutritional status and frailty are significant indicators reflecting physiological reserve. We sought to establish and validate a web‐based calculator containing the Geriatric Nutritional Risk Index (GNRI) and the Tilburg Frailty Indicator (TFI) together with general clinical information to predict total complications among elderly patients with gastric cancer. Methods: This was a prospective cohort study of 582 elderly patients with gastric cancer in a tertiary hospital in China. Nutritional status and frailty were assessed by the GNRI and the TFI, respectively. The nomogram was built and further converted into a web‐based calculator. The receiver operating characteristic analysis was performed to evaluate the discrimination of the nomogram. Calibration was assessed using the calibration curve and Hosmer‐Lemeshow test via the bootstrap resampling procedure. The decision curve analyses (DCAs) were employed to quantify the net benefits of a certain threshold probability for assessing the clinical values. Results: The GNRI (odds ratio [OR], 0.921; 95% confidence interval [CI], 0.895–0.949; P < 0.001), the TFI (OR, 1.243; 95% CI, 1.113–1.386; P < 0.001), surgical approach (OR, 1.913; 95% CI, 1.073–3.408; P = 0.028) and comorbidity (OR = 1.599, 95%CI = 1.028–2.486, P = 0.037) were independently associated with total complications. The nomogram demonstrated good discrimination (area under the receiver operating characteristic curve: training cohort, 0.735; validation cohort, 0.777) and calibration ( P = 0.135). The DCA curves of the nomogram also showed good positive net benefits. Conclusions: The web‐based calculator incorporating the GNRI, the TFI, surgical approach, and comorbidity could successfully predict total complications among elderly patients with gastric cancer with good accuracy in a convenient manner. Geriatr Gerontol Int 2023; 23: 205–212 . Abstract : We constructed a web‐based calculator, which incorporated the GNRI, the TFI, surgical approach, and comorbidity to predict total complications among elderly patients with gastric cancer patients. Such a predictive tool is efficient for risk stratification and convenient for clinical use.